0439 The Effects Of Mindfulness And Relaxation Training For Insomnia (MRTI) On Postmenopausal Women: A Pilot Study. (27th April 2018) - Garcia, M C; Kozasa, E H; Tufik, S; Mello, L A; de Campos, H H
Abstract: Introduction: Our goal is to evaluate the effects of mindfulness meditation training on insomnia and quality of life of postmenopausal women Methods: Thirty postmenopausal women, aged 50–65, not using hormone therapy, and with an apnea-hypopnea index lower than 15 and a diagnosis of insomnia, were randomly assigned to two groups: mindfulness intervention and a control group. They were analyzed before and after 8 weeks of the protocol through questionnaires assessing sleep quality (Pittsburgh Sleep Quality Index - PSQI), insomnia (Insomnia Severity Index ISI), quality of life in menopause (Menopause- Specific Quality of Life - MENQOL), menopausal symptoms (Kupperman Menopausal Index - KMI), level of attention (Mindfulness Awareness Attention Scale - MAAS) as well as assessment through ambulatory polysomnography. This is a pilot study and is limited by its small sample size Results: Significant differences were found in the group that received mindfulness training compared to the control group: improvements in sleep quality, severity of insomnia, quality of life, attention levels and a reduction in menopausal and vasomotor symptoms. We found no differences between the two groups in the evaluation of the polysomnography results. Conclusion: Eight weeks mindfulness meditation training improved the quality of sleep, overall quality of life, level of attention and reduced vasomotor symptoms in postmenopausal women with insomnia. Support (If Any): AFIP, CAPES, CNPQ.